Improved clinical, functional and work outcomes in spondyloarthritides during real-life adalimumab treatment in central–eastern Europe. (August 2016) - Szántó, Sándor; Poór, Gyula; Opris, Daniela; Iaremenko, Oleg; Procházková, Leona; Kuuse, Reet; Nagy, Orsolya; Chernyshov, Valentyn; Géher, Pál
Aim: Adalimumab effectiveness on clinical, functional and work-related outcomes was evaluated in patients with active ankylosing spondylitis or psoriatic arthritis treated in routine clinical practice in central–eastern Europe.Methods: Patients (n = 555) were followed for 12 months. Primary end point was percentage of patients with a treatment response (≥50% decrease from baseline in Bath Ankylosing Spondylitis Disease Activity Index or ≥1.2 point decrease from baseline in Disease Activity Index-28 joint for axial or peripheral symptoms, respectively). Functional status was evaluated by the Bath Ankylosing Spondylitis Functional Index and Health Assessment Questionnaire Disability Index. Working ability was evaluated by the Work Productivity and Activity Impairment Questionnaire − Specific Health Problem.Results: 76.1% of patients with axial symptoms and 83.5% with peripheral symptoms achieved a treatment response. Frequency of extra-articular manifestations decreased. Improvements were observed in functional status and workability. No new safety signals were observed.Conclusion: Adalimumab was effective and well tolerated during real-world use in central–eastern Europe.